2019
DOI: 10.24874/jsscm.2019.13.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Thermal Instability in a Walters’ (Model B') Rotating Nanofluid Saturating a Porous Medium

Abstract: The onset of thermal instability in a dielectric rotating nanofluid layer saturating a porous medium with vertical AC electric field is investigated by employing Darcy model for porous medium. The rheology of the nanofluid is described by Walters' (model B') for calculating the shear stresses from the velocity gradients. The employed model incorporates the combined effects of movement of the molecules of the fluid striking the nanoparticles, thermophoresis and electrophoresis due to the embedded particles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The right-hand side of equation ( 27) is negative if 0, n R  this shows the the medium porosity delays the stationary convection for bottom-heavy configuration and if 0, n R  the medium porosity advances the stationary convection. which is in an agreement with the results derived by Nield and Kuznetsov [4], Chand and Rana [25], Chand et al [28], Rana et al [29] and Ahmad et al [30].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The right-hand side of equation ( 27) is negative if 0, n R  this shows the the medium porosity delays the stationary convection for bottom-heavy configuration and if 0, n R  the medium porosity advances the stationary convection. which is in an agreement with the results derived by Nield and Kuznetsov [4], Chand and Rana [25], Chand et al [28], Rana et al [29] and Ahmad et al [30].…”
Section: Resultssupporting
confidence: 93%
“…Chandrasekhar [17] examined the effect of rotation on the Bénard convection which was later extended by Vadasz [18] for a porous medium layer, and Sharma and Rana [19] studied it for the case of viscoelastic fluid and others [20][21][22][23]. Various researchers have studied the effect of rotation on thermal instability by taking different types of viscoelastic fluids [24][25][26][27][28][29][30], and they found that rotation advances the stationary convection.…”
Section: Introductionmentioning
confidence: 99%
“…Application arises in astronomy and geophysics as well as in connection with numerous engineering problems, such as liquid metal cooling of nuclear reactors, electromagnetic casting of metals, MHD power generation and propulsion. One of the most important applications of this effect is pumping where the main factor responsible for the flow of the fluid is the Lorentz force; its expression is given by the following equation (Al-Habahbeh et al 2016, Reddy et al 2019, Rana et al 2019):…”
Section: Mhd Pumping Theorymentioning
confidence: 99%
“…Maekawa et al 20 studied theoretically the onset of EC on buoyancy and Marangoni convection in a dielectric fluid layer under the influence of AC and DC electric fields. Besides, many studies of ETC have appeared incorporating various other effects, for example, rotation, [21][22][23][24][25][26][27][28] viscoelasticity of the dielectric fluid, [29][30][31] volumetric heat source, [32][33][34] surface tension and variable internal heating, 35 elastico-viscous nanofluid, [36][37][38][39] and so on.…”
Section: Introductionmentioning
confidence: 99%